Dual core processing: MRB1 is an emerging kinetoplast RNA editing complex - Hashimi, Hassan; Zimmer, Sara L; Ammerman, Michelle L; Read, Laurie K; Lukeš, Julius (Trends in parasitology, 2013)
Our understanding of kinetoplastid RNA (kRNA) editing has centered on this paradigm: guide RNAs (gRNAs) provide a blueprint for uridine insertion/deletion into mitochondrial mRNAs by the RNA editing core complex (RECC). The characterization of constituent subunits of the mitochondrial RNA-binding complex 1 (MRB1) implies that it too is vital to the editing process. The recently elucidated MRB1 architecture will be instrumental in putting functional data from individual subunits into context. Our model depicts two functions for MRB1: mediating multi-round kRNA editing by coordinating the exchange of multiple gRNAs required by RECC to edit lengthy regions of mRNAs, and then linking kRNA editing with other RNA processing events.
Keywords: RNA, Guide, Kinetoplastida; Uridine; RNA Editing; RNA, Protozoan; Protozoan Proteins; uridin; Kinetoplastida; RNA, Messenger; editace RNA; guide RNA, Kinetoplastida; RNA protozoální; Trypanosoma brucei brucei; messenger RNA; protozoální proteiny